A synopsis of the 3rd annual Cancer Proteomics Conference. (December 2010) - Mesri, Mehdi; Kinsinger, Christopher; Boja, Emily; Hiltke, Tara; Rahbar, Amir; Rivers, Robert; Rodriguez, Henry
The 3rd annual 'Cancer Proteomics Conference', organized by Select Biosciences (Sudbury, UK), was held in Berlin, Germany, 8–9 June 2010. With the aim of strengthening the links between scientists from Europe, as well as international investigators worldwide, more than 200 delegates attended, representing various countries. The Conference covered many topics in proteomics, including the use of proteomics for cancer therapeutic development, diagnostic applications, biomarker discovery, post-translational modifications and clinical proteomics, as well as new proteomic technologies, which may facilitate future progress. One distinct feature of this meeting was that the Conference was co-located with the 'Advances in Antibody and Peptide Therapeutics' meeting. Delegates had access to both meetings, allowing for enhanced interaction among investigators from the closely linked fields of research.